2018
DOI: 10.3390/vaccines6020021
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of Infection to Adverse Systemic Complications: Periodontal Disease, Toll-Like Receptors, and Other Pattern Recognition Systems

Abstract: Toll-like receptors (TLRs) are a group of pattern recognition receptors (PRRs) that provide innate immune sensing of conserved pathogen-associated molecular patterns (PAMPs) to engage early immune recognition of bacteria, viruses, and protozoa. Furthermore, TLRs provide a conduit for initiation of non-infectious inflammation following the sensing of danger-associated molecular patterns (DAMPs) generated as a consequence of cellular injury. Due to their essential role as DAMP and PAMP sensors, TLR signaling als… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 287 publications
(339 reference statements)
0
45
0
Order By: Relevance
“…An association between cardiovascular (CV) and periodontal diseases has been highlighted in several epidemiological studies (Beukers, Heijden, Wijk, & Loos, ; Gualtero, Lafaurie, & Fontanilla, ; Humphrey, Fu, Buckley, Freeman, & Helfand, ; Kholy, Genco, & Dyke, ; Nazir, ; Reichert et al, ; Tonetti, Van Dyke, & working group 1 of the joint EFP/AAP workshop, ). The relationship between both diseases is based on biological plausibility (Gualtero et al, ; Kholy et al, ; Wallet, Puri, & Gibson, ).…”
Section: Introductionmentioning
confidence: 99%
“…An association between cardiovascular (CV) and periodontal diseases has been highlighted in several epidemiological studies (Beukers, Heijden, Wijk, & Loos, ; Gualtero, Lafaurie, & Fontanilla, ; Humphrey, Fu, Buckley, Freeman, & Helfand, ; Kholy, Genco, & Dyke, ; Nazir, ; Reichert et al, ; Tonetti, Van Dyke, & working group 1 of the joint EFP/AAP workshop, ). The relationship between both diseases is based on biological plausibility (Gualtero et al, ; Kholy et al, ; Wallet, Puri, & Gibson, ).…”
Section: Introductionmentioning
confidence: 99%
“…Various immune cells, including macrophages and DCs, have multiple pathogen recognition receptors (PRRs). TLRs are a family of cell membrane receptors that initiate cellular signal transduction associated with mycobacterial infection [34]. We demonstrated that MAP1889c binds TLR4 molecules in DCs.…”
Section: Discussionmentioning
confidence: 83%
“…TLR -mediated signaling also contribute importantly to cardiovascular disease. For a recent review of this particular subject, see [99] .…”
Section: Effects Of Bacterial Infection Of Vasculaturementioning
confidence: 99%